Justin Martyr's Two Apologies - Ehrhardt, Arnold (The journal of ecclesiastical history, 1953)
It is still an open question whether Justin Martyr wrote two Apologies or only one, and whether the two Apologies which have come down to us under his name in no more than two manuscripts, one the Parisinus Regius 450, the other a Claromontanus, which is only a copy of the first, are composed of the fragments of the one (or two) which he wrote. The evidence is, indeed, at first sight rather bewildering. On the one hand we have the testimony of Eusebius, who refers in his Ecclesiastical History two Apologies, and gives ample quotations from a text very similar to that which has been preserved in the said manuscripts; on the other, not only does Eusebius himself maintain in one instance that the Second Apology was handed in to the emperors Antoninus Pius and Marcus Aurelius, whereas he says elsewhere that it was addressed to the successor of Antoninus Pius, called Antoninus Verus (i.e. to Marcus Aurelius), but he also gives the first place to the Apology which in the Parisinus Regius 450 appears as the second and which in its first chapter shows that it was addressed to Antoninus Pius, Marcus Aurelius and Lucius Verus, and regards that which comes first in the Parisinus Regius 450 as the second. As to the internal evidence, there appears to be a break in both Apologies, in the First Apology after chapter lv and in the Second after chapter xii, after which the argument seems to trail off so that the respective remainders seem to be no more than collections of—sometimes very valuable—fragments.